PENGARUH ANTARA PENGETAHUAN, PERILAKU DAN AKTIVITAS FISIK TERHADAP KEJADIAN HIPERTENSI PADA LANSIA WANITA USIA 55-65 TAHUN DI WILAYAH KERJA PUSKESMAS KUTA RAJA KOTA BANDA ACEH TAHUN 2021: Pengaruh Kejadian Hipertensi pada wanita usia lanjut - Ramadhaniah; Cut Suci Aulia Nanda; Nopa Arlianti (Jurnal Kesehatan, 2021)
The incidence of hypertension greatly interferes with daily activities such as frequentheadaches, feeling tired quickly, easily feeling angry, chest pain, pulse and heartirregularities, especially in the elderly. Hypertension is a health problem that must beprioritized until now. Kuta Raja Community Health Center, Banda Aceh is the highest areaof hypertension cases in the elderly with 88.64% in 2019. This study was purposed todetermine relationship between of knowledge, eating behaviour and physical activity on theincidence of hypertension in the elderly at Kuta Raja Community Health Center, Banda AcehCity. Data collection was carried out using a questionnaire with interview techniques andresearch methods using “case control”. Data was analyzed using the Logistic Regressiontest with the STATA 13 computer program. The result, it was found that knowledge was themost influential risk factor for the incidence of hypertension (OR = 6.90), 95% CI: 2.1-22.0.It is expected that health workers can continue to improve the quality of services and carryout health promotions related to hypertension to the entire community.